Structural performance : probability-based assessement - Cremona, Christian (London : ISTE ; Hoboken, NJ : Wiley, 2011)
This book covers the development of efficient methods for the assessment and the management of civil structures is today a major challenge from economical, social and environmental aspects. Tools for handling uncertainties in loads, geometry, material properties, construction and operating conditions are nowadays essential. Covers the key concepts across topics including probability theory and statistics, structural safety, performance-based assessment, modelling uncertainties and principles of decision theory.
3.1.3. Probability-based approach3.2. Safety and performance principles; 3.2.1. New structures; 3.2.2. Existing structures; 3.3. Invariant measures; 3.4. Reliability theory; 3.4.1. Basic problem; 3.4.2. Convolution integral; 3.4.3. Normal variables; 3.4.4. Geometric expression of the reliability index; 3.4.5. Joint distribution representation; 3.4.6. Limit state with more than two uncorrelated normal variables; 3.4.7. Limit state with correlated variables; 3.5. General formulation; 3.5.1. Failure component -- failure mode; 3.5.2. Safety margins -- limit state functions.
Includes bibliographical references (pages 413-421) and index.
Print version record.
Keywords: Structural analysis (Engineering) -- Statistical methods; Structural failures -- Risk assessment -- Statistical methods; Structural analysis (Engineering) -- Statistical methods; Structural failures -- Risk assessment -- Statistical methods; TECHNOLOGY & ENGINEERING -- Industrial Health & Safety; TECHNOLOGY & ENGINEERING -- Industrial Health & Safety; TECHNOLOGY & ENGINEERING -- Structural; Electronic books